Essays on the history and philosophy of ecological economic thought - Marco Paulo Vianna Franco (2019)
This work aims to contribute to the history and philosophy of ecological economic thought (EET), with a focus on Russian thought and the concept of ecological utopianism. The first essay brings a historical account of EET in the 1880s-1930s, showcasing its intellectual diversity and foundation on social energetics. A scientific metaparadigm was identified, combining different values, methods and ideas into an ecological critique of mainstream economics, comprised of a biophysical approach to economic processes. Bearing in mind such developments, the second essay addresses the body of knowledge produced by Soviet ecology in the 1920s. Research on the links between community ecology, conservation and economic planning revealed how innovative their views were and how well they fit into the definition of ecological utopianism. The third essay acknowledges 19thcentury narodnism not only as one of the intellectual origins of Soviet ecology, but as an important school of EET on its own. The ecological utopianism of Nikolai Chernyshevskii is explained in terms of the extent his ideas were grounded in the natural sciences, and how he envisioned egalitarian social ideals, which would serve as inspiration for the narodnist revolutionary movement. The fourth essay analyzes the ideology of ecological neo-narodnism as a viable alternative to deal with the social and ecological challenges of the 21st century. It is argued that, as political economy, it should move beyond Chaianovian economics to redeem the principles of communality and cooperation of Chernyshevskii. As political ecology, it is a true heir of narodnism; it is best represented by environmental justice movements; it combines the ethnical and local character of peasants’ movements with the need for internationalization; it addresses power relations as a key issue to enforce peasant’s rights; and it adds biophysical limits at the planetary level as a new argument in favor of systemic change.